The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s11899-022-00673-5
|View full text |Cite
|
Sign up to set email alerts
|

Management of Chronic Myeloid Leukemia in Children and Young Adults

Abstract: Purpose of Review Due to lack of pediatric-specific data, the management of chronic myeloid leukemia (CML) in pediatric, adolescents, and young adults is guided by adult CML evidence-based recommendations. Pediatric CML presents differently than adult CML and is often a more aggressive disease with different biological and host factors, yet there is sparse literature on how to address those differences. Recent Findings Over the past two decades, tyrosine k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Chronic myeloid leukemia (CML) is a rare disease in children, accounting for 3% of all pediatric leukemias. 1,2 CML is caused by the t(9;22)(q34;q11.2) translocation, resulting in the BCR::ABL1 fusion oncogene (Ph+). 3…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chronic myeloid leukemia (CML) is a rare disease in children, accounting for 3% of all pediatric leukemias. 1,2 CML is caused by the t(9;22)(q34;q11.2) translocation, resulting in the BCR::ABL1 fusion oncogene (Ph+). 3…”
Section: Introductionmentioning
confidence: 99%
“…15 GI toxicity (mainly diarrhea) may lead to dose reduction during treatment. 2,3,15,16 Animal models showed that bosutinib does not cross the blood-brain barrier, differently from dasatinib. 14…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Currently, only the first-generation TKI, imatinib, and secondgeneration TKIs, dasatinib and nilotinib, are approved by the Food and Drug Administration for pediatric patients. 3 Given the rarity of CML in children, data on long-term treatment profiles and efficacy of TKIs, especially the newer second-and third-generation TKIs, in childhood CML remains scarce. 1 While pediatric oncologists often follow treatment guidelines intended for adults and are increasingly prescribing TKIs in children, there is limited data supporting the generalizability of adult guidelines to children.…”
Section: Introductionmentioning
confidence: 99%
“…TKIs, which inhibit the fusion oncogene BCR‐ABL1 , have significantly improved survival 2 . Currently, only the first‐generation TKI, imatinib, and second‐generation TKIs, dasatinib and nilotinib, are approved by the Food and Drug Administration for pediatric patients 3 . Given the rarity of CML in children, data on long‐term treatment profiles and efficacy of TKIs, especially the newer second‐ and third‐generation TKIs, in childhood CML remains scarce 1 .…”
Section: Introductionmentioning
confidence: 99%